Boron application in clay-loam soil for improved growth, yield and protein contents of mungbean in water-stresses - Maqbool, Rizwan; Ali, Waqar; Nadeem, Muhammad Ather; Abbas, Tasawer (Penerbit Universiti Kebangsaan Malaysia, 2018)
Boron is considered important to improve the drought resistance, yield and protein contents of pulses. Two years of field experiment was conducted to evaluate the effect of boron application and water stress given at vegetative and flowering stages on growth, yield and protein contents of mungbean during spring 2014 and 2015. The experiment was laid out in randomized complete block design with split-plot arrangement giving more emphasis to boron. The experiment comprised three water stress levels (normal irrigation, water stress at vegetative stage and water stress at reproductive phase) and four boron levels (0, 2, 4 and 6 kg ha-1). Final seed yield was significantly increased by different levels of boron application both under normal and water stressed conditions. The increase in yield was mainly due to greater plant height, number of pods bearing branches, number of pods per plant, number of seeds per pod and 1000-grain weight. Boron application at 4 kg ha-1 caused 17%, 10% and 4% increase in grain yield under normal irrigation, stress at vegetative stage and water stress at reproductive phase, respectively. Protein contents were also increased (9-16%) at same boron treatment. Most parameters showed a marked decrease at higher dose (6 kg ha-1) of boron. In conclusion, the boron application at rate of 4 kg ha-1 in clay-loam soil performed the best to enhance mungbean growth, yield and seed protein both under normal and water stressed conditions.